2016
DOI: 10.1111/agec.12316
|View full text |Cite
|
Sign up to set email alerts
|

Economics and politics of food standards, trade, and development#

Abstract: Standards have played an important role in food trade for a very long time. Their rapid growth in recent years has triggered vigorous debates on their impacts on international trade and development, with many arguing that standards are "non-tariff barriers" to trade and that standards are marginalizing the poor. I present conceptual frameworks and review empirical evidence on the equity and efficiency effects and the political economy of standards. Models which incorporate essential aspects of standards yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 96 publications
1
86
0
7
Order By: Relevance
“…A review of some of the literature can be found in Ederington and Ruta (2016) and the review prepared for the Working Party of the Trade Committee (TAD/TC/WP(2017)4). See also Swinnen (2016) for a comprehensive discussion of the trade and development issues.…”
Section: Introductionmentioning
confidence: 99%
“…A review of some of the literature can be found in Ederington and Ruta (2016) and the review prepared for the Working Party of the Trade Committee (TAD/TC/WP(2017)4). See also Swinnen (2016) for a comprehensive discussion of the trade and development issues.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, tariffs may also be preferred by politicians when there are information imperfections in political markets. 37 The choice to complement or substitute tariff interventions with other regulations, such as standards, including labelling and prohibitions, on the wine production process and the use of certain inputs, can be motivated both by economic and political considerations (Marette & Beghin, 2010;Swinnen, 2016). Labelling and the restrictions of certain inputs (such as the use of raisins in wine production or the blending of French wine with imported North African wine) can reduce asymmetric information for consumers or undesirable externalities.…”
Section: Discussionmentioning
confidence: 99%
“…The new equilibrium price is higher than the pre-NTM price (from p to p') (figure 2) and increases consumers' expenditures and producers' revenue. The net effect on domestic welfare depends on the magnitude of gain in utility (for consumers) and revenue (for producers), compared to the size of (negative) effect on consumption expenditures and implementation costs: the higher the consumers' utility, the higher the willingness to pay a higher price; the lower the implementation costs, the higher the gain in revenue (Swinnen 2016).…”
Section: The Rationale Of Non-tariff Measurementioning
confidence: 99%